Experimental Evaluation of the Effect of Chloroform Inhalation as a Method of Euthanasia on the Cerebellum and Hippocampus of Adult Wistar Rats - Samuel, Aguwa Ugochukwu; Nnamdi, Okeke Somadina; Nnabuihe, Ezejindu Darmian; Elizabeth, Eze Chinyere; Ogechi, Azurunwa; Nzube, Obinwa Benedict; Felix, Ovie Ogbo.; Chukwuemeka, Obi Kelvin; Sopuru, Onwuelingo; David, Okonkwo; Ogbuokiri, Doris; Chijioke, Okeke (Technological Innovation in Pharmaceutical Research Vol. 4, 2021)
Chloroform inhalation is a common method of rodent euthanasia in Nigeria for research purposes. This work is designed to evaluate the consequence of this method of sacrifice on the cerebellum and hippocampus of Wistar rats. Twenty male Wistar rats weighing between 160 and 180 were divided into 4 groups of 5 rats each. Group A served as control and was sacrificed using cervical dislocation (a widely acceptable non-inhalation method of sacrifice). Groups B, C and D were exposed to chloroform for 5 minutes once a day (group B), once a day for 2 days and once a day for 3 days. The brains were removed; four from each group was processed for antioxidant assay while one from each group was fixed in Bouin’s fluid for histological studies. Our results show that chloroform inhalation adversely affected the results of the antioxidant parameters studied in a dose-dependent fashion. That means that the adverse effect worsened as the number of days increased. This was also the case with the histology results as there was evidence of cell necrosis in the cerebellar and hippocampal tissues. This also showed dose dependence. We therefore conclude from our results that when studying the brain tissues or carrying out brain related researches, chloroform inhalation is not the method of choice for rat euthanasia. Therefore, chloroform sedation is not ideal for experimental purposes as a method of rat sacrifice, especially when studying rat brain.